Nourishing the brain on deep space missions: nutritional psychiatry in promoting resilience - Pathare, Nihar N.; Fayet-Moore, Flavia; Fogarty, Jennifer A.; Jacka, Felice N.; Strandwitz, Philip; Strangman, Gary E.; Donoviel, Dorit B. (Frontiers in Neural Circuits, 2023)
The grueling psychological demands of a journey into deep space coupled with ever-increasing distances away from home pose a unique problem: how can we best take advantage of the benefits of fresh foods in a place that has none? Here, we consider the biggest challenges associated with our current spaceflight food system, highlight the importance of supporting optimal brain health on missions into deep space, and discuss evidence about food components that impact brain health. We propose a future food system that leverages the gut microbiota that can be individually tailored to best support the brain and mental health of crews on deep space long-duration missions. Working towards this goal, we will also be making investments in sustainable means to nourish the crew that remains here on spaceship Earth.